Myocardial extracellular volume quantification in cardiac CT: comparison of the effects of two different iterative reconstruction algorithms with MRI as a reference standard. - Emoto, Takafumi; Kidoh, Masafumi; Oda, Seitaro; Nakaura, Takeshi; Nagayama, Yasunori; Sasao, Akira; Funama, Yoshinori; Araki, Satoshi; Takashio, Seiji; Sakamoto, Kenji; Yamamoto, Eiichiro; Kaikita, Koichi; et al. (European Radiology, 2020)
Objectives: To compare the effects of hybrid iterative reconstruction (HIR) and model-based iterative reconstruction (MBIR) that incorporates a beam-hardening model for myocardial extracellular volume (ECV) quantification by cardiac CT using MRI as a reference standard.Methods: In this retrospective study, a total of 34 patients were evaluated using cardiac CT and MRI. Paired CT image sets were created using HIR and MBIR with a beam-hardening model. We calculated mean absolute differences and correlations between the global mid-ventricular ECV derived from CT and MRI via Pearson correlation analysis. In addition, we performed qualitative analysis of image noise and beam-hardening artifacts on postcontrast images using a four-point scale: 1 = extensive, 2 = strong, 3 = mild, and 4 = minimal.Results: The mean absolute difference between the ECV derived from CT and MRI for MBIR was significantly smaller than that for HIR (MBIR 3.74 ± 3.59%; HIR 4.95 ± 3.48%, p = 0.034). MBIR improved the correlation between the ECV derived from CT and MRI when compared with HIR (MBIR, r = 0.60, p < 0.001; HIR, r = 0.47, p = 0.006). In qualitative analysis, MBIR significantly reduced image noise and beam-hardening artifacts when compared with HIR ([image noise, MBIR 3.4 ± 0.7; HIR 2.1 ± 0.8, p < 0.001], [beam-hardening artifacts, MBIR 3.8 ± 0.4; HIR 2.6 ± 1.0, p < 0.001]).Conclusions: MBIR with a beam-hardening model effectively reduced image noise and beam-hardening artifacts and improved myocardial ECV quantification when compared with HIR using MRI as a reference standard.Key Points: • MBIR with a beam-hardening model effectively reduced image noise and beam-hardening artifacts. • The mean absolute difference between the global mid-ventricular ECV derived from CT and MRI for MBIR was significantly smaller than that for conventional HIR. • MBIR provided more accurate myocardial CT number and improved ECV quantification when compared with HIR.